Manajemen Pendidikan Terintegrasi untuk Mencapai Keberlanjutan dan Mutu Pendidikan Nasional - Candira W.K, Dedi; Warsah, Idi; Adisel; Warlijasusi, Jumira (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2025)
Integrated educational management plays a vital role in enhancing national education quality, particularly in regions like Kepahiang Regency, which faces challenges of educational disparities between urban and rural schools. This study aims to explore the application of this approach to address such challenges and improve the quality of high school education. Using a descriptive qualitative research method, data were collected through interviews, observations, and documentation studies. The findings reveal that human resource management, curriculum, and infrastructure in Kepahiang schools are not yet fully optimized. Rural schools face limitations in facilities and training opportunities, while urban schools benefit from better resource access. The implemented Merdeka Curriculum shows potential but is hindered by inadequate infrastructure support. This study underscores the importance of collaboration among local governments, schools, and communities to achieve a more holistic and sustainable education system.